Resonant Elements for Tunable Reflectarray Antenna Design. (16th July 2012) - Ismail, M. Y.; Inam, M.
Abstract : This paper presents an accurate analysis of different configurations of reflectarray resonant elements that can be used for the design of passive and tunable reflectarrays. Reflection loss and bandwidth performances of these reflectarray elements have been analyzed in the X-band frequency range with the Finite Integral Method technique, and the results have been verified by the waveguide scattering parameter measurements. The results demonstrate a reduction in the phase errors offering an increased static linear phase range of 225° which allows to improve the bandwidth performance of single layer reflectarray antenna. Moreover a maximum dynamic phase range of 320° and a volume reduction of 22.15% have been demonstrated for a 10 GHz reflectarray element based on the use of rectangular patch with an embedded circular slot.